The Implementation of the Guided Inquiry Model in Basic Chemistry Courses - Cyndi Prasetya; Maisarah Maisarah; Mulyani Mulyani (Chemistry Education Department, 2023)
The study aimed to provide an overview of the application of the model in Basic Chemistry learning and its impact on student abilities. The researchers employed a descriptive qualitative method, focusing on the Guided Inquiry Model applied in Basic Chemistry courses. The primary data source was documentation, administering the data collection technique in the form of documentation analysis involving photos of the Guided Inquiry Model activities. The findings revealed two key points: Firstly, there was an improvement in students' knowledge and insights about basic chemistry, such as recognizing that the purification of substances could effectively separate naphthalene from its contaminants. Secondly, the implementation of the Guided Inquiry Model in Basic Chemistry courses involved four stages. The process began with problem orientation, framed by the question: